Dampak UU No. 18 Tahun 2004 Tentang Perkebunan Terhadap Perubahan Sosial-Budaya Masyarakat (Studi Atas Perkebunan Kelapa Sawit dengan Pola Perkebunan Inti Rakyat di Sumatera Selatan) - Mariatul Qibtiyah (Jurnal Studi Sosial dan Politik, 2017)
The plantation has a great potential in contributing to the economy in Indonesia. So, the government makes a policy in the form of laws No. 18 in 2004 about The Plantations. The ACT of Plantation regulates about the management of the Plantation and a clear legal protection through The Core of People's Plantations (Perkebunan Inti Rakyat/PIR). But the presence of The Plantation ACT is questioned its allignment. The Core of People's Plantations System which has been set up in the ACT of any impact on social change community around the plantations, such as indigenous land that changes into a plantation area, changes in social status, community life, patterns of change value systems in society, and so on.